Middle-Aged Lpaatδ-Deficient Mice Have Altered Metabolic Measures - Michelle Victoria Tomczewski; Maria Fernanda Fernandes; Rajan Singh Grewal; Robin Elaine Duncan (Life, 2022)
Lysophosphatidic acid acyltransferases/acylglycerophosphate acyltransferases (LPAATs/AGPATs) are a group of homologous enzymes that catalyze the formation of phosphatidic acid (PA) from lysophosphatidic acid. We have previously reported that LPAATδ/AGPAT4 localizes to mitochondria, suggesting a potential role in energy metabolism. However, in prior studies of young Lpaatδ-deficient mice (age 9–12 weeks old), we found no differences in body weights, food intakes, activity levels, respiratory gas exchange, or energy expenditure compared to their wildtype (Wt) littermates. To test whether Lpaatδ−/− mice may develop differences in metabolic measures with advancing age, we recorded body weights and food intakes, and used metabolic chambers to assess ambulatory and locomotor activity levels, oxygen consumption (VO2), carbon dioxide production (VCO2), respiratory exchange ratio (RER), and total energy expenditure (heat). Fourteen-month-old Lpaatδ−/− mice had significantly lower mean body weights compared to Wt littermate controls (44.6 ± 1.08 g vs. 53.5 ± 0.42 g, respectively), but no significant differences in food intake or activity levels. This phenotypic difference was accompanied by significantly elevated 24 h daily, and 12 h light and dark photoperiod average VO2 (~20% higher) and VCO2 (~30% higher) measures, as well as higher RER and total energy expenditure (heat) values compared to Wt control littermates. Thus, an age-related metabolic phenotype is evident in Lpaatδ−/− mice. Future studies should examine the role of the lipid-modifying enzyme LPAATδ across the lifespan for greater insight into its role in normal and pathophysiology.